1996
DOI: 10.1016/s0021-9290(96)80022-4
|View full text |Cite
|
Sign up to set email alerts
|

A global verification study of a quasi-static knee model with multi-bundle ligaments

Abstract: Abstract-The ligaments of the knee consist of fiber bundles with variable orientations, lengths and mechanical properties. In concept, however, these structures were too often seen as homogeneous structures, which are either stretched or slack during knee motions. In previous studies, we proposed a new structural concept of the ligaments of the knee. In this concept, the ligaments were considered as multi-bundle structures, with nonuniform mechanical properties and zero force lengths. The purpose of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Sixteen input parameters were included in the optimization: ALC and PFL initial strain and stiffness, localized LCL and sMCL strain (anterior, middle, posterior bundles), LCL and sMCL stiffness (applied to all bundles), and inferior-superior and anterior-posterior LCL and sMCL femoral attachment locations. Strain for each ligament during the optimization was bounded at 74% Arms et al, 1983); stiffness for each ligament was varied within values reported in the literature (Arms et al, 1983;Griffith et al, 2009;Mommersteeg et al, 1996;LaPrade et al, 2004). Although the specimen-specific LCL and MCL tibial and femoral attachment sites were identified through dissection, the fibers carrying load throughout the passive femoral flexion range were unknown and could exist anywhere within the attachment footprint.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Sixteen input parameters were included in the optimization: ALC and PFL initial strain and stiffness, localized LCL and sMCL strain (anterior, middle, posterior bundles), LCL and sMCL stiffness (applied to all bundles), and inferior-superior and anterior-posterior LCL and sMCL femoral attachment locations. Strain for each ligament during the optimization was bounded at 74% Arms et al, 1983); stiffness for each ligament was varied within values reported in the literature (Arms et al, 1983;Griffith et al, 2009;Mommersteeg et al, 1996;LaPrade et al, 2004). Although the specimen-specific LCL and MCL tibial and femoral attachment sites were identified through dissection, the fibers carrying load throughout the passive femoral flexion range were unknown and could exist anywhere within the attachment footprint.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Gillespie and Dickey (2004) demonstrated this principle in showing that transverse loads from the interspinous ligament significantly increase the stiffness of the SSL. Furthermore, other investigators have demonstrated the necessity of quantifying the inhomogeneous material properties of ligaments in order to accurately determine their physiologic response (Momersteeg et al, 1995;Mommersteeg et al, 1996Mommersteeg et al, , 1997. However, despite these findings, no anisotropic, inhomogeneous, material constitutive data has been reported for the SSL.…”
Section: Introductionmentioning
confidence: 99%
“…Engin and Tumer (1993) developed a two-dimensional dynamic model of the knee that included a patella. Blankevoort and Huiskes (1995) and Mommersteeg et al (1996) developed and experimentally verified a threedimensional knee model with surrounding soft tissue. Sathasivam and Walker (1997) developed a rigid body analysis of TKR that reproduced motions found using the Stanmore knee simulator .…”
Section: Introductionmentioning
confidence: 99%